Subverting Traditional Gender Roles in Contemporary English Poetry: The World’s Wife by Carol Ann Duffy Mike and Honey by Rupi Kaur Ariel by Sylvia Plath - Ali, Shakir Hussein (Integrated Journal for Research in Arts and Humanities, 2024)
Generally speaking, male poets depict women in their poetry as typically seen as frail, weak, and reliant on males. However, in this paper we will examine the how women are portrayed in the same way in the poetry written by female poets, which is shocking. The purpose of this article is to examine how women use poetry to create their own gender identities. The language used by female poets to establish their own identities and the themes they chose for their poems reveal how they see themselves in relation to the other gender. The article 'data are derived from an analysis selection of three English-language poems written by female poets: the world's wife by Carol Ann Duffy, Mike and Honey by Rupi Kaur, and Ariel by Sylvia Plath. To thoroughly examine how gender identity is constructed.